Optical dating of K-feldspar grains from Middle Pleistocene lacustrine sediment at Marathousa 1 (Greece). (20th December 2018) - Jacobs, Zenobia; Li, Bo; Karkanas, Panagiotis; Tourloukis, Vangelis; Thompson, Nick; Panagopoulou, Eleni; Harvati, Katerina
Abstract: Post-infrared infrared stimulated luminescence (pIRIR) measurements are reported for multiple aliquots of potassium-rich feldspar grains from sedimentary deposits at Marathousa 1 and Choremi Mine in the Megalopolis Basin in southern Greece. Ages were obtained for 9 samples from the deposits that over- and underlie as well as include the archaeological and palaeontological deposits at Marathousa 1. These sediments are sandwiched between lignite seams II and III and thought to represent sediment deposition during a single glacial period. A single age was obtained for a sample from Choremi mine. The equivalent dose estimates are based on a newly developed method presented elsewhere, and environmental dose rate determinations followed standard procedures. A specific focus of this paper is the determination of a representative estimate of time-averaged palaeo-water content of the organic and sand-rich deposits and the impact of porosity and compaction on these estimates. Ages are presented using two water content scenarios. These final ages have relatively large uncertainties, making it difficult to accurately assign deposition to a single oxygen isotope stage (OIS). Taking uncertainty into account, sediment deposition at Marathousa 1 occur sometime during OIS 12 and 11 and at Choremi mine during MIS 8. When combined with other proxy information, these results support the interpretation that the peat deposits (represented by lignite seams II and III) were deposited during warm interglacial periods, and that the intervening clastic materials were deposited during glacial periods. In this case, the ages are best interpreted as supporting deposition of sediments during MIS12. This is consistent with one of the proposed age models, but younger than the other.